2002
DOI: 10.1182/blood.v99.5.1860
|View full text |Cite
|
Sign up to set email alerts
|

Ph+ acute lymphoblastic leukemia resistant to the tyrosine kinase inhibitor STI571 has a unique BCR-ABL gene mutation

Abstract: The tyrosine kinase inhibitor STI571 is a promising agent for the treatment of advanced Philadelphia chromosome positive (Ph ؉ ) acute lymphoblastic leukemia (ALL), but resistance develops rapidly in most patients after an initial response. To identify mechanisms of resistance to STI571, 30 complementary DNAs (including 9 matched samples) obtained from the bone marrow of individuals with Ph ؉ ALL were analyzed by direct sequencing of a 714-base pair region of ABL encoding for the adenosine triphosphate (ATP)-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(148 citation statements)
references
References 17 publications
4
141
0
3
Order By: Relevance
“…Low-level bcr-abl mutations have been detected with variable frequency in imatinib-naïve patients with Ph þ ALL both at initial diagnosis and at the time of recurrence after prior therapy. 12,16,19 The significantly lower response rate and shorter TTP in the latter group suggest that the relative contribution of TKD mutations to resistance may vary by disease history and extent of prior therapy. The inferior efficacy of imatinib in patients with advanced Ph þ ALL could thus be due to non-mutational resistance mechanisms induced by prior chemotherapy, or alternatively by a higher frequency of pre-existing mutations, a preponderance of mutations with greater transforming activity or a larger mutant clone size at the start of treatment with TKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-level bcr-abl mutations have been detected with variable frequency in imatinib-naïve patients with Ph þ ALL both at initial diagnosis and at the time of recurrence after prior therapy. 12,16,19 The significantly lower response rate and shorter TTP in the latter group suggest that the relative contribution of TKD mutations to resistance may vary by disease history and extent of prior therapy. The inferior efficacy of imatinib in patients with advanced Ph þ ALL could thus be due to non-mutational resistance mechanisms induced by prior chemotherapy, or alternatively by a higher frequency of pre-existing mutations, a preponderance of mutations with greater transforming activity or a larger mutant clone size at the start of treatment with TKI.…”
Section: Discussionmentioning
confidence: 99%
“…12 --21 Bcr-abl mutations may pre-exist at low levels in a subset of patients with relapsed Ph þ ALL before salvage therapy with imatinib, and they have also been detected with variable frequency in imatinib-naïve patients with newly diagnosed Ph þ ALL. 12,16,19 Although no mutations were detected in 12 patients using standard sequencing or pyrosequencing for the T315I and Y253H mutations, 14 a more sensitive cloning and sequencing approach used by Soverini et al 19 showed the presence of low frequency TKD mutations in all imatinib-naïve patients analyzed. This study identified a broad spectrum of mutations, most of which have not been linked to clinical resistance.…”
Section: Introductionmentioning
confidence: 99%
“…However, clinical and experimental observations reveal that resistance to the drug has become a rising problem (Weisberg and Griffin, 2001;Gorre and Sawyers, 2002). Resistance may be achieved by enhanced expression of the kinase (Mahon et al, 2000;Gorre and Sawyers, 2002;Hochhaus et al, 2002), blocking of the drug (Gambacorti-Passerini et al, 2000), reduction of cellular concentration of the drug (Mahon et al, 2003) and also by mutations in the BCR/ABL gene (Mahon et al, 2000;Branford et al, 2002;Gorre and Sawyers, 2002;Hofmann et al, 2002;Azam et al, 2003). The latter phenomenon appears to play a major role in IM resistance of Ph þ leukemias (Hochhaus et al, 2002); however, the mechanisms causing mutations are not known.…”
Section: Facilitation Of Genomic Instabilitymentioning
confidence: 99%
“…Thus far, reports of de novo imatinib-resistance in vivo have implicated only Bcr-Abl overexpression or mutations in its kinase domain resulting in persistent phosphotyrosine signaling. 13,14,[29][30][31][32][33][34] Extension of our investigation into primary cells revealed that, in general, loss of in vivo response to imatinib is not associated with failure of other chemotherapeutic drugs to inhibit progenitor cell colony formation. The lack of in vitro Leukemia response to imatinib in the primary material harvested prior to exposure of the patient to imatinib might be interpreted as innate resistance to the drug.…”
Section: Figurementioning
confidence: 99%